SCHOOL ADMINISTRATORS’ UTILIZATION OF MANAGEMENT INFORMATION SYSTEM FOR ADMINISTRATIVE EFFECTIVENESS IN SECONDARY SCHOOLS IN ENUGU EDUCATION ZONE - Chidinmachinenye, Thompson; Anachuna, ObinnaNonso (International Journal of Research -GRANTHAALAYAH, 2019)
The study ascertained school administrators’ utilization of management information system for administrative effectiveness in secondary schools in Enugu Education Zone. Two specific purposes were formulated and two research questions guided the study. Descriptive survey design was adopted for the study. The population of the study comprised all the 31 principals in public secondary schools in Enugu education zone. A 14 items researcher developed instrument titled; School Administrators’ utilization Management Information System Questionnaire (SAMISQ) was used for data collection. The instrument was structured on a four rating scale of Strongly Agree (SA), Agree (A), Disagree (D) and Strongly Disagree (SD) weighted 4, 3, 2 and 1 respectively. The instrument was face validated by three research experts. The Cronbach alpha was used to determine the reliability of the instrument which yielded a high reliability coefficient value of 0.82. Data were analyzed using mean and standard deviation. The findings revealed among others that school administrators’ do not utilize management information system for students’ personnel administration in secondary schools by not; allowing students to apply for admission online, processing students results using spreadsheet software, managing students attendance using spreadsheet software, disseminating information to students and parent through the school website, encouraging teachers to issue home assignment to student using email system, and encouraging multi-media instructional delivery using PowerPoint software application. Thus, the study recommended among others that the Government through the State Ministry of Education should organize seminars and workshop for secondary school administrators in order to train them on the utilization of management information system for student personnel administration. Conclusion was drawn based on the findings.